(untitled) (Revista Inclusiones, 2020)
Psychological and pedagogical training is insignificant at military educational institutions, so its results do not meet the needs of the armed forces as to a high level of psychological and pedagogical competence of officers who are in constant contact with servicemen while training and educating them. One way to solve this problem is to intensify the practical component of psychological, pedagogical or leadership courses by using role-playing games when cadets give mini-lectures and psychological workshops. Substantiation of expediency and study of use of the specified role-playing games makes the purpose of the research which tasks include defining the essence of psychological and pedagogical competence of future army officers, substantiation of the significance and experimental check of the efficiency of role-playing games as conditions of effective means for developing the specified competence.